Analysis of Sectoral Contributions and Intersectoral Linkages in The Economy of Bali Province: An Input-Output and Multiplier Product Matrix Approach - Luh Made Arisusanti; I Nyoman Mahaendra Yasa (Journal of Business, Social and Technology, 2026)
Background: Regional economic development aims to improve community welfare through a productive and sustainable economic structure. Bali Province still shows a high dependence on the service sector, particularly tourism, making it vulnerable to external shocks such as the COVID-19 pandemic. Objective: This study aims to analyze the contribution of economic sectors, forward and backward linkages, dispersion power, degree of sensitivity, and output, income, and labor multipliers in Bali Province. Methods: This study uses a quantitative approach with Input-Output analysis and the Multiplier Product Matrix (MPM). The data were obtained from the 2016 Input-Output Table of Bali Province, updated to 2024 using the RAS method. Results: The findings show that Bali’s economic structure is still dominated by the service sector, particularly the accommodation and food service sector, which serves as the main contributor to output, gross value added, and final demand. The accommodation and food service sector has the strongest forward linkages (index = 4.671), while the electricity and gas supply sector has the highest backward linkages (index = 1.892) and serves as a key sector in the economy. The multiplier analysis indicates that the accommodation and food service sector has the highest output multiplier (2.341), the financial and insurance services sector has the highest income multiplier (1.756), and the wholesale and retail trade sector has the highest labor multiplier (3.124). Conclusion: Bali’s economic development needs to continue strengthening the tourism sector as a leading sector, while also promoting economic diversification and strengthening strategic sectors to sustainably enhance regional economic resilience.